Pseudobithynia ambrakis Glöer, Falniowski & Pešić 2010 (Gastropoda: Rissooidea: Bithyniidae), a new species from the Macedonian part of Dojran Lake - Slavevska-Stamenković, Valentina; Glöer, Peter; Hinić, Jelena; Mitić-Kopanja, Danijela; Pešić, Vladimir (Institute for Biodiversity and Ecology, 2021)
The recently described freshwater gastropod Pseudobithynia ambrakis Glöer, Falniowski & Pešić 2010 is reported from the R. North Macedonia for the first time. The species was previously known only from Lake Amvrakia in Greece, but it turned out to be present in Dojran Lake as well, only misidentified and recognized under different name, Bithynia leachii (Sheppard, 1823). In the following paper we present information about the species’ habitat and distribution. Photographs of the shell and male genitalia are also provided.